Targeting GRP78 and antiestrogen resistance in breast cancer. (June 2013) - Cook, Katherine L; Clarke, Pamela AG; Clarke, Robert
Breast cancer is the most prevalent cancer in women, with over 200, 000 new cases diagnosed each year. Over 70% of breast cancers express the estrogen receptor-α, and drugs targeting these receptors such as tamoxifen or Faslodex ® often fail to cure these patients. Many estrogen receptor-positive tumors lose drug sensitivity, making endocrine resistance a major clinical problem. Recently, investigation into the molecular mechanisms of endocrine resistance has highlighted a causative role of the unfolded protein response in antiestrogen resistance. In particular, the master regulator of the unfolded protein response, GRP78, was observed to be elevated in endocrine-resistant breast cancer and directly affected antiestrogen therapy responsiveness. GRP78 was found to impact many different cellular processes that may affect breast cancer survival. Recently, various compounds have been reported to affect GRP78 activity and it may be advantageous to combine these drugs with antiestrogens to overcome endocrine therapy resistance.